Experimental and numerical studies to estimate fatigue crack growth behavior of Ni-based super alloy. (August 2018) - Kumar, M.; Ahmad, S.; Singh, I.V.; Rao, A.V.; Kumar, J.; Kumar, V.
Highlights: J-decomposition approach in conjunction with XFEM is successfully used to compute the SIFs for individual modes. Mode-I and Mode-II SIFs are calculated by decoupling of stress, strain and displacement field. Fatigue life at elevated temperature (650 °C) nearly becomes one-third in comparison to fatigue life at RT (26 °C). FCGR at elevated temperature (650 °C) remains nearly same at both the frequencies i.e. 10 Hz and 1 Hz. J IC fractographs show a cleavage type fracture initially, and a dimple type rupture during final stage of crack growth. Abstract: In this work, the fatigue crack growth behavior of the Nickel based super alloy is investigated at room (26 °C) and elevated temperature (650 °C). The fatigue crack growth experiments are performed to understand the effect of temperature and loading rate. The elasto plastic fracture toughness tests are performed to evaluate J IC . Paris law is used in conjunction with extended finite element method (XFEM) to numerically predict the fatigue life. The stress intensity factors of individual mode ( K I and K II ) are computed from J -integral by decomposing the stress, strain and strain derivatives into symmetric and antisymmetric parts. Few parametric studies are performed to show the mesh convergence and path independency of J -integral. Fatigue crack growth in an aero-engine turbine disc is predicted. The numerically predicted fatigue life is found in good match with the experimental results.